KAJIAN BENTUK DAN KOMPOSISI GERAK TARI IYO-IYO DI MASYARAKAT TANJUNG PAUH MUDIK KABUPATEN KERINCI - Oktania, Rahma; Indrayuda, Indrayuda (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research aims to describe and analyse the form and composition of the Iyo-Iyo dance in the community of Tanjung Pauh Mudik. This study is qualitative research with a descriptive method. The instruments for this research are the researcher themselves, assisted by supporting instruments such as writing tools, audio-visual media, and a camera. Data were collected through literature study, observation, interviews, and documentation. The steps for analysing the data include data collection, data reduction, data presentation, and data verification. The results of the research indicate that the form of the Iyo-Iyo dance in the community of Tanjung Pauh Mudik, Kerinci Regency, consists of space, time, and energy, while the movement composition of the Iyo-Iyo dance includes motif, phrase, sentence, and cluster. The spatial aspect of the Iyo-Iyo dance is limited yet meaningful, where simple floor patterns such as straight lines or semi-circular formations are used to create order and symbolise balance within the customary social structure. The temporal aspect of the Iyo-Iyo dance moves at a moderate to fast tempo, with a repetitive rhythmic pattern that aligns with traditional accompanying musical instruments, thus creating a meditative atmosphere filled with cultural awareness. The energy aspect of the Iyo-Iyo dance uses moderate energy that is conveyed gently and controlled. The movement composition of the Iyo-Iyo dance consists of three parts: the opening, the core, and the closing. The opening part features gestures of respect and welcoming, the core part conveys the essential values or messages of the customs, and the closing part marks the end of the performed rite. This arrangement not only clarifies the structure of the performance, but also demonstrates the narrative continuity that has been maintained from generation to generation. It can be concluded that the form and arrangement of the Iyo-Iyo dance movements are a true reflection of the social, spiritual, and aesthetic values that thrive within the indigenous community of Kerinci. The profound lyrical movements and the dominance of hand usage make this dance not only visually beautiful but also culturally meaningful. Therefore, the Iyo-Iyo dance deserves to be preserved and continually introduced to the younger generation as part of the cultural heritage that enriches the identity of the Indonesian nation.